2022
DOI: 10.1016/j.jcis.2021.06.178
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surfactant mass transfer with drop formation times from dynamic interfacial tension measurements in microchannels

Abstract: The developed methodology measures dynamic interfacial tension down to 3ms. Surfactant adsorption times can be significant if compared to drop formation times. Dynamic interfacial tension was observed even with small-molecule surfactants. The proposed criteria ensure equilibrium interfacial tension during drop formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 63 publications
3
42
0
Order By: Relevance
“…SI 5 †), and it is found that the adsorption time (at the interface) is longer than the diffusion time (from the bulk phase to the subinterface), which is in line with literature. 10 This indicates that at these higher concentrations, surfactant mass transfer is either mixed diffusion-kinetic controlled 32 or purely kinetic-controlled. 11 Besides, as the interface gradually approaches saturation (e.g., at τ ≈ 1 s), the free energy barrier for adsorption may also slow down the adsorption rate of SDS monomers, which also gives rise to the transition from diffusion-to kinetic-controlled mass transfer mechanism.…”
Section: Methods Performancementioning
confidence: 98%
“…SI 5 †), and it is found that the adsorption time (at the interface) is longer than the diffusion time (from the bulk phase to the subinterface), which is in line with literature. 10 This indicates that at these higher concentrations, surfactant mass transfer is either mixed diffusion-kinetic controlled 32 or purely kinetic-controlled. 11 Besides, as the interface gradually approaches saturation (e.g., at τ ≈ 1 s), the free energy barrier for adsorption may also slow down the adsorption rate of SDS monomers, which also gives rise to the transition from diffusion-to kinetic-controlled mass transfer mechanism.…”
Section: Methods Performancementioning
confidence: 98%
“…As recently shown by Kalli and Angeli 48 , it is preferred to use the dynamic interfacial tension instead of the equilibrium value, to generate universal flow pattern maps. However, it can be difficult to obtain an accurate estimation of the dynamic interfacial tension for forming droplets because classical methods based on a fixed interface (as pendant drop tensiometry or force tensiometry) may not be representative 17 . Moreover, it was shown in the previous section that γ seems to have a small impact on the BRANN prediction.…”
Section: Effect Of Reduced Inputsmentioning
confidence: 99%
“…3.9% 7.3% 6.4% 3.9% 6.1% 5.2% ED: experimental data, SD: synthetic data size data set was produced. To predict the dimensionless droplet diameter for various flow rates, surfactant type and surfactant concentration, two data-driven models (BRANN and XGBoost) were used and compared to a recent semi-empirical model 17 .…”
Section: Validation Of Synthetic Data In the Laboratorymentioning
confidence: 99%
See 2 more Smart Citations